Protein kinase C potentiation of N-methyl-d-aspartate receptor activity is not mediated by phosphorylation of N-methyl-d-aspartate receptor subunits - Zheng, Xin (The National Academy of Sciences, 1999)
N-methyl-d-aspartate receptors (NMDARs) are Ca(2+)-permeable glutamate-gated ion channels whose physiological properties in neurons are modulated by protein kinase C (PKC). The present study was undertaken to determine the role in PKC-induced potentiation of the NR1 and NR2A C-terminal tails, which serve as targets of PKC phosphorylation [Tingley, W. G., Ehlers, M. D., Kameyama, K., Doherty, C., Ptak, J. B., Riley, C. T. & Huganir, R. L. (1997) J. Biol. Chem. 272, 5157–5166]. Serine residue 890 in the C1 cassette is a primary target of PKC phosphorylation and a critical residue in receptor clustering at the membrane. We report herein that the presence of the C1 cassette reduces PKC potentiation and that mutation of Ser-890 significantly restores PKC potentiation. Splicing out or deletion of other C-terminal cassettes singly or in combination had little or no effect on PKC potentiation. Moreover, experiments involving truncation mutants reveal the unexpected finding that NMDARs assembled from subunits lacking all known sites of PKC phosphorylation can show PKC potentiation. These results indicate that PKC-induced potentiation of NMDAR activity does not occur by direct phosphorylation of the receptor protein but rather of associated targeting, anchoring, or signaling protein(s). PKC potentiation of NMDAR function is likely to be an important mode of NMDAR regulation in vivo and may play a role in NMDA-dependent long-term potentiation.